Analyzing of Student Alcohol Consumption and Consequences - Semić, Aid (International Journal of Data Science, 2024)
Student alcohol consumption is very interesting topic today. It is known that average number of students who consume alcohol today is rapidly increasing. Here is idea to analyze how it affect their studying and grades. To predict the grades of students we have to take a lot of aspect in consideration. This research uses a range of different parameters and machine learning algorithms, such as Exploratory Data Analysis and XGBoost. By using this methodologies and algorithms I have to admit that I didn’t develop the best model for prediction.